SHARED PARENTING VS SOLE CUSTODY IN MALAYSIAN SHARIAH COURTS: LESSONS FROM COVID-19 (International Seminar on Syariah and Law (INSLA), 2021)
When it comes to child custody, the predominant standard practised by Malaysian Shariah Courts has always been the best interest of the child. Aside from specific conditions, the custodianship is often granted to the mother. The non-custodial parent, often being the father, is generally given visitation and overnight rights by the court while carrying the duty for child maintenance despite his limited rights. With the global outbreak of Covid-19, family institutions are greatly affected physically, mentally, and financially. The untimely separation of children from their parents under child custody cases raises the question of whether these children's rights are rightfully attended to or not. According to UNICEF, among the children who are profoundly affected by Covid-19 are single-parent children and female-headed households. The situation becomes dire as the consequences of Covid-19 continue to influence the care and child maintenance of a divorcee's child. Hence, this article aims to propose shared parenting as an alternative to ensure child's rights are cared for considering Shariah Courts have no explicit jurisdiction to order for joint custody. Through a doctrinal approach and library research, this article examines the concepts of shared parenting as an 'evolution' to joint custody. The article also discusses prospective benefits and challenges of implementing the idea of shared parenting in Shariah Courts. In conclusion, emphasis on the significance of shared parenting is highlighted as the best and fair solution to attain the best interests of a child at the same time promoting amicable relationships and understanding between divorced couples.